Analisis Pengaruh Kapasitas Fiskal Terhadap Belanja Modal di Provinsi Aceh - Farid Alfasyah; Puti Andiny; Yani Rizal; Safuridar Safuridar (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study analyses the influence of fiscal capacity on capital expenditure in Aceh Province over the period 2007-2023 by collecting data from the BPS website of Aceh Province. Using multiple linear regression method, this study found that Local Own Revenue (PAD), Revenue Sharing Fund (DBH), and Special Allocation Fund (DAK) have a positive and significant influence on capital expenditure. The results of the analysis show that every 1 unit increase in PAD, DBH, and DAK respectively increases capital expenditure by 234.0927 units, 57.51575 units, and 25.09292 units. This finding indicates that stronger fiscal capacity allows local governments to allocate more budget for infrastructure and investment projects, which support economic development and community welfare. Increased personnel expenditure was also found to have a significant positive impact on capital expenditure, indicating the importance of investment in human resources to support the efficiency and effectiveness of managing development projects. These results support the Human Capital and Administrative Efficiency theories, which assert that competent and efficient human resources increase productivity in budget management